Factor Analysis Of Delay Return Empty Container To Depo - Sianturi, Intan; Aini Rakhman, Rizqi; Nugraha, Bugi (Publisher Cv. Inara, 2023)
This research was conducted to determine the factors that influence delays in returning containers to shipping company depots. Because delays in returning empty containers can result in some containers not being able to be used for the next shipment because they have not been returned to the depot, so the goods have to wait to be loaded into the container. This type of research uses qualitative research, by conducting an interview with one of the shipping company employees, then processing it using a fish bone diagram or Ishikawa diagram so that the author can find out the causes and effects of why the container was returned to the depot late. The problems faced by shipping companies are delays in returning empty containers, which results from late payments to shipping companies, full consignee factory/warehouse conditions, difficult permits from the relevant authorities due to expiration and so on. Efforts that need to be made to prevent this are by providing a time limit for processing the return of empty containers, the need for other alternatives if there is a buildup in the consignee warehouse by appointing another party as the unloading location, as well as increasing the competency of human resources who are directly involved in cargo handling.